Evaluating the quality of services for bus performance in Alor Setars - Norhisham S.; Bakar M.F.A.; Syamsir A.; Zaini N.; Baharin N.L.; Shkuri N.S.M.; Saad N.M. (IOP Publishing Ltd, 2023)
Bus transportation; Buses; Disasters; Quality of service; Traffic congestion; Hours of services; On-time performance; Passenger loads; Public transport; Quality services; Service frequency; Service Quality; Transit capacity; Telecommunication services